The medical and psychological morbidity of patients with urogenital fistulae - Srichand, Pushpa (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To analyze the frequency of medical and psychological morbidity of patients with urogenital fistulae. There are many complications related to childbirth and gynaecological surgeries. Urogenital fistula is one of the worst complications. The women suffer from significant medical and psychological morbidity. These issues need to be addressed at every forum. Methods: A descriptive study was carried out at Liaquat University Hospital and Isra University Hospital Hyderabad Pakistan from 01/06/2007 to 30/06/2018. 520 patients with urogenital fistulae were managed. A pre-designed performa was used to record the details about medical and psycho-social consequences. Data was analyzed, results were described as frequency and percentage. Results: During the study period 520 confirmed cases of urinary fistulae were managed. Regarding psychological health all (100%) patients had major degree depression. 511 (98%) patients were found socially isolated. 458 (88%) patients were malnourished. 338 (65%) had severe excoriation of vulva, bladder and vaginal calculi were present 25 (4.8%) patients. Majority of the patients were suffered social, verbal and physical abuse. Conclusions: Patients with urogenital fistulae are not only having the surgical morbidity but they do suffer significant medical and social morbidity. There is a definite need to address these under looked miseries by a devoted fistulae team work in collaboration with social workers, religious leaders and healthcare providers to bring life back to these patients.